La calata dei Lanzichenecchi nei Promessi sposi (Gilgameš, 2016)
The essay examines the invasion of landsknechts as the most intensive Manzoni’s blame on war not only in The Betrothed but in all his previous works. The comparison between the novel and his tragedies focuses on the role of victory and enlightens the narrative strategies used to represent the militia. Although Manzoni’s disagreement to unjustified conflicts is already present in the tragedies, only the novel denies any form of moral stature to commanders and soldiers and no military virtue is given to them by the Author. But Manzoni juxtaposes a new form of heroism to this completely negative representation of mercenaries. In the small band of men headed by the Nameless and fighting for their freedom and their properties is portrayed the only war that can be considered right, according to Manzoni. However, in the Nameless’s choice of fighting without weapons, the blame on any injury comes back to prove the Manzoni’s conflicting point of view on war.